An Integrative Analysis of Green Accounting Practices in Multinational Companies in Developing Countries - Tindage, Jalmijn; Solissa, Ferdinando; Astuty, Putu Anggreyani Widya; Turot, Margaretha (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Green accounting has become a strategic approach to supporting sustainable business practices, particularly amidst increasing global pressure on corporate environmental responsibility. This study aims to integratively analyze green accounting practices implemented by multinational corporations (MNCs) in developing countries. Using a qualitative method with a library research approach, this study collected and analyzed various academic sources, company reports, and international policy documents relevant to environmental accounting. The results show that the implementation of green accounting by MNCs in developing countries remains highly variable, depending on local regulations, stakeholder pressure, and corporate commitment to sustainability. The most common practices include recording environmental costs, reporting carbon emissions, and disclosing investments in environmentally friendly technologies. However, significant challenges remain, such as limited binding legal frameworks, low environmental accounting literacy, and a lack of integration between financial and sustainability reporting. This integrative analysis demonstrates that the adoption of green accounting is not merely a technical issue but also a reflection of broader corporate governance, transparency, and social responsibility. This study recommends the need for harmonization of environmental reporting standards, capacity building of local human resources, and cross-sector collaboration to promote greener and more accountable accounting practices in developing countries.